Induction of Apoptosis Coupled to Endoplasmic Reticulum Stress through Regulation of CHOP and JNK in Bone Marrow Mesenchymal Stem Cells from Patients with Systemic Lupus Erythematosus - Genkai Guo; Yan Meng; Wei Tan; Yunfei Xia; Chun Cheng; Xiaolan Chen; Zhifeng Gu (Journal of Immunology Research)
Previous studies indicated that bone marrow mesenchymal stem cells (BM-MSCs) from patients with systemic lupus erythematosus (SLE) exhibited the phenomenon of apoptosis. In this study, we aimed to investigate whether apoptosis of BM-MSCs from SLE patients were dysregulated. In this paper, endoplasmic reticulum stress (ERS) was evidenced by increased expression of phosphorylated protein kinase RNA-like ER kinase (PERK) and inositol-requiring protein-1 (IRE-1). We also found the activation of downstream target eukaryotic translation initiator factor 2α (eIF 2α) and CCAAT/enhancer-binding protein- (C/EBP-) homologous protein (CHOP) in BM-MSCs from SLE patients. Interestingly, we discovered that 4-phenylbutyric acid (4-PBA), a selective inhibitor of ERS, blocked the apoptosis of BM-MSCs from SLE patients and alleviated the level of Jun N-terminal kinase1/2 (JNK1/2) and CHOP. Furthermore, blockage of PERK signaling expression by siRNA not only significantly reduced the expression of CHOP, but also activated the anti-apoptotic regulator B-cell lymphoma-2 (Bcl-2). Blockage of IRE-1 or JNK1/2 by siRNA resulted in the decreased expression of JNK1/2 and proapoptosis protein Bcl-2 associated protein X (BAX). These results implicated that ERS-mediated apoptosis was a critical determinant of BM-MSCs from SLE patients.